Discovery of tert -Butyl Ester Based 6-Diazo-5-oxo- l -norleucine Prodrugs for Enhanced Metabolic Stability and Tumor Delivery - Novotná, Kateřina; Tenora, Lukáš; Prchalová, Eva; Paule, James; Alt, Jesse; Veeravalli, Vijay; Lam, Jenny; Wu, Ying; Šnajdr, Ivan; Gori, Sadakatali; Mettu, Vijaya Saradhi; Tsukamoto, Takashi; et al. (Journal of medicinal chemistry, 2023)
The glutamine antagonist 6-diazo-5-oxo-l-norleucine (DON) exhibits remarkable anticancer efficacy; however, its therapeutic potential is hindered by its toxicity to gastrointestinal (GI) tissues. We recently reported the discovery of DRP-104, a tumor-targeted DON prodrug with excellent efficacy and tolerability, which is currently in clinical trials. However, DRP-104 exhibits limited aqueous solubility, and the instability of its isopropyl ester promoiety leads to the formation of an inactive M1-metabolite, reducing overall systemic prodrug exposure. Herein, we aimed to synthesize DON prodrugs with various ester and amide promoieties with improved solubility, GI stability, and DON tumor delivery. Twenty-one prodrugs were synthesized and characterized in stability and pharmacokinetics studies. Of these, P11, tert-butyl-(S)-6-diazo-2-((S)-2-(2-(dimethylamino)acetamido)-3-phenylpropanamido)-5-oxo-hexanoate, showed excellent metabolic stability in plasma and intestinal homogenate, high aqueous solubility, and high tumor DON exposures and preserved the ideal tumor-targeting profile of DRP-104. In conclusion, we report a new generation of glutamine antagonist prodrugs with improved physicochemical and pharmacokinetic attributes.